The combination therapy with esomeprazole and flupenthixol/melitracen in symptom improvement of erosive gastritis complicated with negative feelings compared with Esomeprazole alone - Hu, Lidan; Shen, Liandong; Li, Dechuan; Huang, Min; Xiao, Xingpeng; Chen, Shengquan (Cellular and Molecular Biology, 2020)
The purpose of this study was to evaluate the co-prescription efficacy of esomeprazole and flupenthixol/melitracen relative to that of solitary esomeprazole on erosive gastritis complicated with negative feelings. 140 erosive gastritis patients complicated with negative feelings enrolled in the present study. Seventy cases in the control group took esomeprazole, and 70 cases in the observation group received esomeprazole plus flupenthixol/Melitracen, both for 4 weeks. We gastroscopically checked the clinical symptoms, mucosal erosion, PGE2 and MDA levels in gastric mucosa, anxiety, depression, and recurrence before and after treatment in the groups. After treatment, the observation group had lower scores of clinical symptoms, mucosal erosions, Hamilton Depression Rating Scale (HAMD), and Hamilton Depression Rating Scale (HAMA) than the control group (p<0.05); as well, the observation group showed higher PGE2 and lower MDA levels than the control group (p<0.05); during six months of follow-up (100% follow-up rate), 16 and 34 recurrent cases occurred, respectively, in the observation and control groups (p<0.05). Co-prescription of esomeprazole and flupenthixol/melitracen improved the clinical symptoms and mucosal erosions, relieved negative feelings and reduced the recurrence rate. The efficacy of the co-prescription is higher than that of the solitary prescription.